2021
DOI: 10.3390/v13061067
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tocilizumab Therapy in Different Subtypes of COVID-19 Cytokine Storm Syndrome

Abstract: Background: Cytokine storm in COVID-19 is heterogenous. There are at least three subtypes: cytokine release syndrome (CRS), macrophage activation syndrome (MAS), and sepsis. Methods: A retrospective study comprising 276 patients with SARS-CoV-2 pneumonia. All patients were tested for ferritin, interleukin-6, D-Dimer, fibrinogen, calcitonin, and C-reactive protein. According to the diagnostic criteria, three groups of patients with different subtypes of cytokine storm syndrome were identified: MAS, CRS or sepsi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Regarding IL-6 blockade with tocilizumab in COVID-19-associated MAS, the results are controversial. Some studies have reported that treatment with tocilizumab contributes to reduced mortality and favorable outcomes [144,145]. Conversely, another study noted that tocilizumab demonstrated limited efficacy for COVID-19-related MAS [146].…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Regarding IL-6 blockade with tocilizumab in COVID-19-associated MAS, the results are controversial. Some studies have reported that treatment with tocilizumab contributes to reduced mortality and favorable outcomes [144,145]. Conversely, another study noted that tocilizumab demonstrated limited efficacy for COVID-19-related MAS [146].…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…This, in turn, drives the overexpression of proinflammatory cytokines such as IL-6 [ 511 ], and chemokines such as IL-8 (aka CXCL8 [C-X-C motif chemokine ligand 8]) [ 512 , 513 ]. The lymphopenia usually appears within the first week of infection, whereas the cytokine storm, typically associated with macrophage activation, typically occurs later as the disease progresses [ 514 ]. Nevertheless, there may be a link between these two processes, as it has been demonstrated that neutralization of IL-6 helped to restore circulatory T-cell counts [ 515 ].…”
Section: Antibodies For Palliative Therapymentioning
confidence: 99%
“…40,41 A recent double-blind placebo-controlled study of seven days of sildenafil in acutely ill patients with COVID-19 found five-fold decreased mortality and halving in ITU admissions in the PDE5I group, suggesting an important role in acute COVID infection and a need for further studies. 42…”
Section: Prevention Of Diabetic Peripheral Neuropathymentioning
confidence: 99%